Early neuropathology of somatostatin/NPY GABAergic cells in the hippocampus of a PS1xAPP transgenic model of Alzheimer's disease. - Ramos, Blanca; Baglietto-Vargas, David; del Rio, Juan Carlos; Moreno-González, Inés; Santa-Maria, Consuelo; Jiménez, Sebastián; Caballero, Cristina; López-Téllez, Juan Félix; Khan, Zafar U.; Ruano, Diego; Gutiérrez-Pérez, Antonia; Vitorica Ferrández, Javier; et al. (Elsevier, 2006)
At advanced stages, Alzheimer's disease (AD) is characterized by an extensive neuronal loss. However, the early neurodegenerative deficiencies have not been yet identified. Here we report an extensive, selective and early neurodegeneration of the dendritic inhibitory interneurons (oriens-lacunosum moleculare, O-LM, and hilar perforant path-associated, HIPP, cells) in the hippocampus of a transgenic PS1 × APP AD model. At 6 months of age, from 22 different pre- and postsynaptic mRNA markers tested (including GABAergic, glutamatergic and cholinergic markers), only the expression of somatostatin (SOM) and NPY neuropeptides (O-LM and HIPP markers) displayed a significant decrease. Stereological cell counting demonstrated a profound diminution (50–60%) of SOM-immunopositive neurons, preceding the pyramidal cell loss in this AD model. SOM population co-expressing NPY was the most damaged cell subset. Furthermore, a linear correlation between SOM and/or NPY deficiency and Abeta content was also observed. Though the molecular mechanism of SOM neuronal loss remains to be determined, these findings might represent an early hippocampal neuropathology. Therefore, SOM and NPY neuropeptides could constitute important biomarkers to assess the efficacy of potential early AD treatments.
Keywords: Alzheimer, Enfermedad de; Alzheimer’s disease; Neurodegeneration; Transgenic mice; Biomarkers; Hippocampus; Interneurons; Cholinergic; Glutamatergic; GABAergic